Interventional pulmonology procedures in the pediatric population. Issue 6 (8th July 2013) - Gilbert, Christopher R.; Feller‐Kopman, David; Akulian, Jason; Hayes, Margaret; Yarmus, Lonny
Summary Introduction Advanced training in interventional pulmonology (IP) includes a multidisciplinary approach to a wide variety of pathologic conditions affecting different age groups. The role of the interventional pulmonologist in the pediatric patient population has not been described. We report our experience of the care of pediatric patients by IP at an academic institution. Methods A retrospective review of inpatient and outpatient IP procedures from 2008 to 2011 was performed. All patients' less than 21 years of age at the time of their procedure were identified. Data regarding age, procedure performed, pre‐operative diagnosis, results, and complications were collected. Results Thirty‐five patients younger than the age of 21, with 14 of these patients being under the age of 18, were identified. Fifty‐six procedures were performed on the entire cohort, 30 as inpatient procedures and 26 as outpatient procedures. There were no deaths or major complications related to any procedure. Discussion We identified a cohort of pediatric patients that were able to successfully undergo diagnostic and therapeutic procedures under the direction of an experienced IP team. Cases included the evaluation and management of both malignant and benign complex airway and pleural diseases. There was no major morbidity or mortality related to our procedures, demonstrating an ability to safely evaluate and manage complex airway and pleural disease in the pediatric population. Pediatr Pulmonol. 2014; 49:597–604. © 2013 Wiley Periodicals, Inc.